Blockchain Advancements to Sustainable IT Systems - Ziyang Chen; Mia Gibbs (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The modern digital economy relies heavily on information technology (IT) systems to support communication, business, entertainment and more. However, the expanding digital footprint of society also comes with significant environmental costs. IT infrastructure and operations currently account for up to 1.5% of global greenhouse gas emissions (Belkhir & Elmeligi, 2018). Electronic waste from discarded hardware is also rising sharply, with over 53 million metric tons generated globally in 2019 alone (Forti et al., 2020). As IT systems continue to scale up to meet the world's growing digital demands, their sustainability impacts are becoming impossible to ignore. New approaches are urgently needed to maintain essential IT services for society, while also reducing associated energy usage, waste, and other environmental burdens. Blockchain technology, with its decentralized and transparent architecture, presents a promising pathway to develop more sustainable IT systems for the future. This paper provides a comprehensive review of how blockchain innovations can promote sustainability across IT infrastructure, operations and supply chains. First, the fundamental architecture and attributes of blockchain technology are outlined. Next, emerging use cases and applications where blockchain can optimize sustainability of IT systems are analyzed in depth. Key opportunities and challenges for blockchain integration are discussed, along with a forward outlook on the technology's future development and adoption trends.